Primary preventive potential for stroke by avoidance of major lifestyle risk factors - Tikk, Kaja; Groß-Weissmann, Marie-Luise; Kloss, Manja; Kaaks, Rudolf (Stroke, 2014)
Background and Purpose: Because primary prevention of stroke is a priority, our aim was to assess the primary preventive potential of major lifestyle risk factors for stroke in middle-aged women and men. Methods: Among 23 927 persons, 551 (195 women and 356 men) had a first diagnosis of stroke during an average follow-up of 12.7 years. Using Cox proportional hazards models, we estimated the associations of adiposity, smoking, physical activity, alcohol consumption, and diet with risk of developing stroke. A competing risk model built from cause-specific proportional hazards models accounting for concurrent risk of death was used to calculate relative and absolute reductions in stroke occurrences that could have been achieved by maintaining a healthy lifestyle pattern. Results: Obesity, smoking, alcohol consumption, diet, and physical inactivity were each identified as modifiable lifestyle risk factors for stroke. About 38% of stroke cases were estimated as preventable through adherence to a healthy lifestyle profile (never smoking, maintaining optimal body mass index and waist circumference, performing physical exercise, consuming a moderate quantity of alcohol, and following a healthy dietary pattern). Age-specific estimates of 5-year incidence rates for stroke in the actual cohort and in a hypothetical, comparable cohort of individuals following a healthy lifestyle would be reduced from 153 to 94 per 100 000 women and from 261 to 161 per 100 000 men for the age group 60 to 65 years. Conclusions: Our analysis confirms the strong primary prevention potential for stroke based on avoidance of excess body weight, smoking, heavy alcohol consumption, unhealthy diet, and physical inactivity.